Search for production of WW/WZ resonances decaying to a lepton, neutrino and jets in pp collisions at s√ = 8 TeV with the ATLAS detector - Onofre, A. (2015)
A search is presented for a narrow diboson resonances decaying to WW or WZ in the final state where one W boson decays leptonically (to an electron or a muon plus a neutrino) and the other W/Z boson decays hadronically. The analysis is performed using an integrated luminosity of 20.3 fb−1 of pp collisions at s√ = 8 TeV collected by the ATLAS detector at the LHC. No evidence for resonant diboson production is observed, and resonance masses below 700 GeV and 1490 GeV are excluded at 95% confidence level for the spin-2 Randall-Sundrum bulk graviton G∗ with coupling constant of 1.0 and the extended gauge model W′ boson respectively.